Decision Frequency and Synchronization Across Agents: Implications for Aggregate Consumption and Equity Return - Lynch, Anthony W. (Journal of Finance, 1996)
This article examines a model in which decisions are made at fixed intervals and are unsynchronized across agents. Agents choose nondurable consumption and portfolio composition, and either or both can be chosen infrequently. A small utility cost is associated with both decisions being made infrequently. Calibrating returns to the U.S. economy, less frequent and unsynchronized decision-making delivers the low volatility of aggregate consumption growth and its low correlation with equity return found in U.S. data. Allowing portfolio rebalancing to occur every period has a negligible impact on the joint behavior of aggregate consumption and returns.